Discovering the Byzantine Art of Building: Lectures at the RIBA, the Royal Academy and the London Architectural Society, 1843–58. (2020) - Karydis, Nikolaos
ABSTRACT: Although British architects played a major role in the rediscovery of the Byzantine monuments of Greece in the late nineteenth and early twentieth centuries, earlier interest in the subject has remained obscure. Four lectures, read at the Royal Institute of British Architects, the Royal Academy and the London Architectural Society from 1843 to 1857, reflect a lively interest in Byzantine church architecture in the mid-nineteenth century. Delivered by Charles Robert Cockerell (1843), Edwin Nash (1847), Thomas Leverton Donaldson (1853) and John Louis Petit (1858), these lectures constitute some of the earliest attempts in England to explore both well-known monuments such as Hagia Sophia and lesser-known churches in Greece, Turkey and elsewhere. The manuscript records of these lectures show that influential British architects were not only familiar with Byzantine monuments, but were also able to look at them from the viewpoint of the designer and the builder. Emphasising the potential of Byzantine architecture to inform new design, they paved the way for the Byzantine revival, half a century later, and for the systematic investigation of Byzantine architecture from the late nineteenth century onwards.